THE EFFECTIVENESS OF TEACHING READING NEWS ITEM TEXT BY USING DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY AT THE FIRST GRADE OF MAN KRECEK PARE - Maghfiroh, Lailatul (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study aims at knowing how the DRTA strategy affects the reading ability of the first grade students of MAN Krecek Kediri in comprehending news item text. The research design which is used in this research was descriptive quantitative experimental with one group pre-test and post-test design.  The subjects of this research were students from X IPS 3. The instruments used were pre-test and post-test. The data gotten were statistically computed by SPSS. The result of this study showed that t-test is 5,307. Itâ€™s higher than t.table at 1% significancy level. So, it can be concluded that teaching reading news item text by using DRTA strategy is effective.